Multidisciplinary treatment for patients with stage IV gastric cancer: the role of conversion surgery following chemotherapy - Beom, Seung-Hoon (BMC Cancer, 2018)
BACKGROUND: With advances in gastric cancer chemotherapy, conversion surgery has drawn attention as a new strategy to improve the outcome of stage IV disease. We investigated the efficacy of conversion surgery following chemotherapy for patients with stage IV gastric cancer. METHODS: We retrospectively reviewed clinico-pathologic variables and oncologic outcomes for 101 patients with stage IV gastric cancer who were treated with systemic chemotherapy followed by gastrectomy with intension of curative resection from January 2005 to December 2012. RESULTS: In terms of the best response from palliative chemotherapy, complete or partial response were observed in 65 patients (64.4%) in overall. Complete response of metastatic site were observed in 72 (71.3%) and 66 (65.3%) patients as best and pre-operative response, respectively. The overall complete macroscopic resection, rate was 56.4%. Eleven patients (10.9%) received combined metastasectomy. There was no postoperative surgery-related mortality for 1 month. The median overall survival time was 26.0 months. Multivariable analysis identified complete macroscopic resection, chemotherapy response (complete response/partial response) of metastatic sites, and change in CEA level as independent prognostic factors contributing to overall survival. CONCLUSIONS: Patients with stage IV gastric cancer who exhibit a good clinical response to chemotherapy might obtain greater survival benefit from gastrectomy following chemotherapy compared with patients who exhibit a poor response to chemotherapy. Prospective, randomized trials are required to determine the best strategy for combining initial chemotherapy with subsequent gastrectomy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-018-4998-x) contains supplementary material, which is available to authorized users.